Development of Engineered Water Reservoirs for Aedes Mosquito Breeding Control - Aidil Onasis; Jihad Wafiqa Rahmah; Rahmi Hidayanti; Akhirul Desman; Evino Sugriarta; Awalia Gusti (CV. Get Press Indonesia, 2025)
The presence of water reservoirs as mosquito breeding sites is a major factor in the transmission of dengue hemorrhagic fever (DHF). This study developed an engineering-based tool to manage larval density and prevent mosquito proliferation. Experiments were conducted using 18 water reservoirs made of fiber, concrete, metal, and plastic, both with and without larval traps, with 900 Aedes aegypti larvae as samples. Data were analyzed using univariate and bivariate methods (T-test) at a 95% confidence level. Results showed no significant difference among container materials in supporting mosquito breeding, allowing flexibility in designing water containers for vector control. A light sensor was later integrated to detect larval presence, and a model for community-based application was introduced. The findings confirm that all types of water storage, regardless of material or size, can support mosquito breeding. Incorporating technologies such as light or motion sensors can enhance larval control efforts. This model also serves as a tool for public education on environmental health, emphasizing the importance of household conditions in preventing mosquito proliferation. Further research will refine and implement the model in real-world settings.